The ketogenic diet in the treatment of diabetes type 2 - Karolina Raksa; Mateusz Pawlina; Karolina Ziętara; Martyna Lewkowicz; Katarzyna Nowakowska; Przemysław Raczkiewicz (Kazimierz Wielki University, 2022)
Despite  advances in the medical world, obesity remains a major worldwide health hazard .The majority of chronic diseases like diabetes is largely related to obesity which is usually a product of an unhealthy lifestyle and poor dietary habits. The ketogenic diet has become an increasingly popular approach for both weight loss and as an alternative diet for type 2 diabetes mellitus (T2DM). In addition, this diet has a positive effect on body weight, blood glucose level, glycosylated hemoglobin and plasma lipid profile. This review focuses on the therapeutic effectiveness of using LCKD for the treatment of type 2 diabetes.